Computer Society e-Learning Site Usage Up. (Computer (00189162), 2008)
This article presents information on the use of the Institute of Electrical & Electronics Engineers Inc. (IEEE) Computer Society e-Learning campus Web site. The variety of courses available for continuing education on the IEEE Web site including introductions to computer programming with C++, ethical hacking, and project management skills are discussed. Curricula in computer software development that terminate in professional credentials are also discussed. Guidebooks and technical volumes on computing offered through the site are promoted.